Ministernotomy Thymectomy in Mysthania Gravis-Future - Suraj Wasudeo Nagre; K N Bhosle (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2017)
A thymectomy is the surgical removal of the thymus gland. The thymus has been demonstrated to play a role in the development of MG. It is removed in an effort to improve the weakness caused by MG, and to remove a thymoma if present.About 10% of MG patients have a tumor of the thymus called a thymoma. Most of these tumors are benign and tend to grow very slowly; on occasion they are malignant ("cancerous").A thymectomy is recommended for patients under the age of 60 (occasionally older) with moderate to severe MG weakness. It is sometimes recommended for patients with relatively mild weakness, especially if there is weakness of the respiratory (breathing) or oropharyngeal (swallowing) muscles. It is also recommended for all patients with a thymoma. A thymectomy is usually not recommended for patients with weakness limited to the eye muscles (ocular myasthenia gravis). The neurological goals of a thymectomy are signifi cant improvement in the patient's weakness, reduction in the medications being employed, and ideally eventually a permanent remission (complete elimination of all weakness off all medications). There are three basic surgical approaches transternal, transcervical and videoscopic[VATS] thymectomy each with several variations. Regardless of the technique employed, the surgical goal is to remove the entire thymus. Many believe this should include removal of the adjacent fat; others are less sure.Here we give our study report of comparision between full sternotomy against ministernotomy thymectomy patients preopt, intraopt and postopt factors, fifteen patients each in two group with ten year experience.